3D kinematic analysis of overarm movements for different sports - Meric, B.; Aydin, M.; Colak, T.; Özbek, A.; Bulgan, C. (Kinesiology, 2009)
The aim of this study was to compare the kinematics of the overarm throw for different sports. Eleven elite female handball players and nine elite female volleyball players were selected as subjects for the study. Arm and forearm segment movement in the backswing and acceleration phases of players performing the volleyball spike and the handball jump shot were evaluated. Video data were captured using two Sony 50Hz cameras and were digitized and analyzed using Simi Motion Analysis 5.5 program. In the backswing phase, there were significant differences in the angular width, velocity and acceleration between the volleyball players and handball players on the transverse, vertical, and sagittal planes of the motions (p<.01). In the acceleration phase, the statistically significant difference was found in the angular width of the arm segment motion on the transverse plane (p<.05). On the sagittal plane, the significant difference was found in the angular width, velocity, and acceleration of the arm motions between the volleyball and handball players (p<.05). These results suggest that volleyball players use vertical flexion more frequently, thus increasing the time to gain velocity. Handball players transfer the velocity used in horizontal flexion to the vertical flexion in a short period of time.